KEY ASPECTS OF USING LOW-FREQUENCY PIEZOELECTRIC THROMBOELASTOGRAPHY AS A DYNAMIC METHOD OF ASSESSING THE STATE OF THE HEMOSTASIS SYSTEM IN REAL TIME - Tarabrin, O. O.; Vrublevska, S. V.; Maksymets, T. O. (Rehabilitation and Recreation, 2024)
A condition that leads to the development of venous or arterial thrombosis and its consequences is considered prothrombotic. In the biological regularity of the system of regulation of the aggregate state of blood (RASK) under thrombohazard, in the broad sense of this word, one should understand the incoherence of the PACK subsystems, which makes it impossible to ensure the discreteness of the hemostatic potential in different areas of the blood flow adequately to the conditions formed in them. Venous thromboembolism is the most common vascular disease after acute myocardial infarction and stroke. According to a number of authors, the frequency of objectively confirmed in-hospital deep vein thrombosis (DVT) reaches approximately 10 to 40% among patients undergoing general surgery and 40 to 60% after major orthopedic operations. In 25–30% of patients, the thrombosis affects the deep veins, causing DVT and can lead to pulmonary embolism (PE). In surgical and orthopedic patients, PE occurs in 10% of patients and is the main cause of hospital deaths. Despite conducting many studies of the blood coagulation system, cases of thromboembolic complications in patients who are at risk of thrombotic complications are becoming more and more frequent. In cases where it is necessary to obtain a dynamic picture of the blood coagulation system, for example, cardiovascular surgery, obstetric bleeding, severe injuries, etc. This article reflects the technique of low-frequency piezoelectric thromboelastography, its practical value and examples of using the NPTEG method. In addition, the methods of using NPTEG to detect the degree of risk of thrombotic danger in patients included in the risk group are displayed. Conclusion. Thromboelastography, in particular NPTEG, is an effective method of assessing hemostatic potential, which, unlike standard laboratory tests, provides a detailed picture of the hemostasis system in graphic and numerical form, and a larger number of indicators makes it possible to determine disorders in a specific link of the hemostasis system. Thus, NPTEG is an effective method of assessing hemostasis to determine therapeutic tactics and the risk of thrombo-hemorrhagic disorders in patients with changes in hemostatic potential.